1996
DOI: 10.1016/s0960-9822(02)00454-2
|View full text |Cite
|
Sign up to set email alerts
|

A new family of regulators of G-protein-coupled receptors?

Abstract: Organisms as diverse as fungi and humans use G-protein-coupled receptors to control signal transduction pathways responsive to various hormones, neuroregulatory molecules and other sensory stimuli. Continual stimulation of these receptors often leads to their desensitization, which is mediated in part by the consecutive actions of two families of proteins--the G-protein-coupled receptor kinases, which phosphorylate the agonist-occupied receptors, and the arrestin proteins, which subsequently bind to the recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(140 citation statements)
references
References 8 publications
2
135
0
2
Order By: Relevance
“…Interestingly, Siderovski et al (17) identified sequence homology between RGS domains and an ϳ120 residue region in the N terminus of GRKs through a BLAST search of the NCBI protein data base (17). Indeed, both GRK2 and GRK3 (residues 51-173) are ϳ20% identical and ϳ30% similar to various RGS domains (Fig.…”
Section: Homology Between the N Terminus Of Grks And Rgs Domains-whermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Siderovski et al (17) identified sequence homology between RGS domains and an ϳ120 residue region in the N terminus of GRKs through a BLAST search of the NCBI protein data base (17). Indeed, both GRK2 and GRK3 (residues 51-173) are ϳ20% identical and ϳ30% similar to various RGS domains (Fig.…”
Section: Homology Between the N Terminus Of Grks And Rgs Domains-whermentioning
confidence: 99%
“…In general, these RGS proteins interact with the ␣ subunits of the G i and G q families (10,11,16). In addition, a small collection of proteins including GRKs (17), axin (18), D-AKAP (19), and p115 Rho-GEF (20,21) have been identified as having somewhat less conserved RGS domains. Recently, one of these atypical RGS proteins, p115 Rho-GEF, was shown to function as a selective GAP for G␣ 12/13 suggesting that sequence differences in these RGS proteins may correlate with different preferences for G protein-binding partners (20,21).…”
mentioning
confidence: 99%
“…Although the mutated residues were spread over the entire NH 2 -terminal region, there are particularly high concentrations of mutations localized to the first 10 residues and to the central portion of the NH 2 -terminal domain (residues 72 to 87) suggesting the functional importance of these regions. Although GRK5 interaction with G␣ subunits has not been reported, this central region falls within the regulator of G protein signaling (RGS) homology domain in GRKs (encompassing residues ϳ40 -180 in GRK5) that mediates GRK2 interaction with G␣ q (31)(32)(33)(34). Glu-72, Pro-75, and Val-87 may be particularly important because multiple clones were identified with these residues mutated.…”
Section: Figmentioning
confidence: 99%
“…All RGS family members share sequence similarity that extends over approximately 130 aa, separated in some cases by insertions of varying length (9)(10)(11). This conserved RGS domain is sufficient to stimulate GTPase activity of G protein ␣ subunits in vitro (12)(13)(14).…”
mentioning
confidence: 99%